Mechanisms of some Lactobacillus sp. for enhancing the growth of mulberry silkworm, Bombyx mori larvae, and their role as biocontrol agents against diseases - Radwa G. Attia; Marwa N. Moustafa; Shireen A. M. Ma’moun; Hayam, A. E. Sayed; Doaa R. Abdel-Haleem (Egyptian Journal of Biological Pest Control)
Abstract Background One of the most important problems facing the silk industry in Egypt is the existence of a good hybrid that can withstand fluctuations in climatic change, which is the main reason for silkworm susceptibility to bacterial infection. Results This study focused on the impact of feeding the silkworm larvae from the last day of the 3rd larval instar till the 1st day of the 5th larval instar on three species of lactic acid bacteria: Lactobacillus acidophilus, Lactobacillus casei, and Lactobacillus delbrueckii. Three different concentrations (106, 107, and 108 CFU/ml) of each species were evaluated individually as treatment during the rearing season to reduce the expectation of diseases. The results indicated that each Lactobacillus sp. has improved the immune system of the silkworm, to some extent. Accordingly, treated larvae were more resistant to pathogens, as observed in low mortality records relative to control. Scanning electron micrograph of larval foregut revealed the association of Lactobacillus sp., as solitary and colonized bacterial cells, within crypts of the crop region and their attachment to its wall by biofilaments. Histochemical analysis of the silk gland at the end of the 5th larval instar showed great enhancement in fibroin and sericin production in treated silkworms with all tested probiotics, especially Lactobacillus acidophilus compared to untreated ones. Conclusion Overall, incorporating Lactobacillus sp. into silkworm-rearing diets represents a hopeful strategy to boost their growth, health, and productivity, also fostering sustainable practices in sericulture.